Glocal Symposium on Information and Social Sciences (GSISS) 2023 / Perpustakaan Tengku Anis - UiTM Kelantan, Perpustakaan Tengku Anis (Perpustakaan Tengku Anis, 2023)
The School of Information Science, College of Computing, Informatics & Media UiTM Cawangan Kelantan in collaboration with the Faculty of Administrative Sciences and Policy Studies, Faculty of Law and Perpustakaan Tengku Anis (PTA) have successfully organized Glocal Symposium on Information and Social Sciences (GSISS) 2023. This symposium was held on 20th and 21st June 2023 at HRDA, UiTM Cawangan Kelantan starting at 8:00 AM until 5:00 PM. With the theme "Information and Social Sciences: Challenges and Opportunities in the Digital Era", this symposium was organised in hybrid mode to give participants options and increase event exibility.